Two schemes for producing molecular ions on a bent graphene layers - Poklonski, Nikolai A.; Ratkevich, Sergey V.; Vyrko, Sergey A.; Vlassov, Anatoli T. (Journal of the Belarusian State University. Physics, 2023)
A brief review of methods for producing molecular ions is given, on the basis of which two original schemes for generation of a flow of negatively and positively charged ions from a flow of electrically neutral molecules scattered on electrically conductive bent graphene layers are proposed. When graphene layers are bent, the densities of p-electrons of carbon atoms are redistributed, and a deformation-induced electric dipole moment appears in the direction perpendicular to the bent surface. The presented schemes differ in the mutual arrangement of the bent graphene layers relative to the flow of molecules. Quantum chemical calculations using the PM7 semiempirical method provide estimates of the electron affinity and ionisation energy (potential) of a number of molecules (C60, O2, H2O, CO2, etc.) suitable for production of molecular ions from them according to the proposed schemes. If a molecule is scattered on a negatively charged graphene side, then due to the transfer of an electron from graphene to the molecule, the molecule acquires a negative charge. If a molecule is scattered on a positively charged graphene side, then due to the transfer of an electron from the molecule to graphene, the molecule acquires a positive charge. To obtain molecular ions, it is necessary to select molecules with values of electron affinity (to obtain negative ions) or ionisation energy (to obtain positive ions) close to the work function of graphene (≈ 4.3 eV).